Navigating an academic career : a brief guide for PhD students, postdocs, and new faculty - McDonnell, Jeffrey J. (Special publication (American Geophysical Union), 2020)
With the number of people being awarded PhDs growing far more rapidly than the supply of academic jobs, those at an early-career stage must think strategically in order to be competitive and successful. Navigating an Academic Career: A Brief Guide for PhD students, Post docs, and New Faculty is a concise and conversational manual that guides readers through starting their academic journey, surviving the demands of their first academic position, and thriving in academia and beyond